Mir106b-25 and Mir17-92 Are Crucially Involved in the Development of Experimental Neuroinflammation - Finardi, Annamaria; Diceglie, Martina; Carbone, Luca; Arnò, Caterina; Mandelli, Alessandra; De Santis, Giuseppe; Fedeli, Maya; Dellabona, Paolo; Casorati, Giulia; Furlan, Roberto (Frontiers in Neurology, 2020)
MicroRNAs (miRNAs) are single-stranded RNA that have key roles in the development of the immune system and are involved in the pathogenesis of various autoimmune diseases. We previously demonstrated that two members of the miR106b-25 cluster and the miR17-92 paralog cluster were upregulated in T regulatory cells from multiple sclerosis (MS) patients. The aim of the present work was to clarify the impact of miR106b-25 and miR17-92 clusters in MS pathogenesis. Here, we show that the mice lacking miR17-92 or both miR106b-25 and miR17-92 (double knockout) are protected from Experimental Autoimmune Encephalomyelitis (EAE) development while depletion of miR106b-25 only does not influence EAE susceptibility. We suggest that the absence of miR106b does not protect mice because of a mechanism of compensation of miR17-92 clusters. Moreover, the decrease of neuroinflammation was found to be associated with a significant downregulation of pro-inflammatory cytokines (GM-CSF, IFNγ and IL-17) in the spinal cord of double knockout EAE mice and a reduction of Th17 inflammatory cells. These results elucidate the effect of miR106b-25 and miR17-92 deletion in MS pathogenesis and suggest that their targeted inhibition may have therapeutic effect on disease course.